PERIPHERAL BLOOD NEUTROPHIL-TO-LYMPHOCYTE RATIO (NLR) AND PLATELET-TO-LYMPHOCYTE RATIO (PLR) IN POST-KIDNEY TRANSPLANT PATIENTS WITH GRAFT REJECTION ACCORDING TO THE BANFF 2023 CLASSIFICATION (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in the diagnosis of rejection after kidney transplantation. Subjects and methods: A cross-sectional descriptive study was conducted on 132 kidney transplant patients at Military Hospital 103 (January 2023–December 2025), including 59 patients with rejection (the gold standard was histopathological rejection according to Banff 2022) and 73 patients with stable kidney transplants. NLR and PLR were calculated from complete blood counts; analysis was performed using SPSS 22. Results: The rejection group showed impaired renal function and increased inflammatory markers. NLR was higher in the rejection group compared to the group with stable kidney function (6.94 ± 2.19 vs. 2.19 ± 0.09; p < 0.05), and PLR was higher in the rejection group compared to the group with stable kidney function (204.4 ± 13.35 vs. 2.19 ± 0.09; p < 0.05). There were no differences between TCMR and ABMR, nor were any significant differences observed with the Banff 2022 histological indices. Conclusion: NLR and PLR are elevated in patients with kidney rejection; NLR, PLR is valuable for supporting diagnosis, useful for differentiation, and a suggestive marker for biopsy; neither showed a significant correlation with the degree of histological damage according to Banff 2022.
Keywords: NLR; PLR; rejection; Kidney allograft biopsy; Banff 2023.